Genetic relationship among indigenous sheep population of Bangladesh - Deb, GK; Choudhury, MP; Kabir, MA; Khan, MYA; Ershaduzzaman, M; Nahar, TN; Hossain, SMJ; Alam, MS; Alim, MA (Bangladesh Journal of Animal Science, 2019)
The study was conducted to investigate the genetic relationships among indigenous sheep population of Bangladesh (Barind, Jamuna river basin, Coastal and Garole sheep) using microsatellite markers. A total of 96 blood samples were collected from adult sheep of Barind (24), Jamuna River Basin (24), Coastal (24), Garole(10) and available Chotanagpuri (10) sheep. Chotanagpuri sheep was used as an outgroup population. DNA was extracted from blood samples using QIAGEN DNA Mini extraction kit and was quantified using a nanodrop. FAO recommended 13 labeled microsatellite markers were used for polymerase chain reaction (PCR). PCR product was confirmed by 2% agarose gel electrophoresis and visualized by staining with ethidium bromide.The exact allele sizes in each primer were determined by GeneMaker V1.85 demo. Microsatellite tool kit and Dispan software package were used for calculation of allele frequency, number of alleles per locus, observed and expected heterozygosity and genetic distances (DA). The Dispan software was used to calculate inter-individual genetic distances. These distance values were used to construct an UPGMA tree. Results showed that average number of polymorphic alleles per locus varied from4 in HUJ616 to 12 in MAF70. Observed heterozygosity was also varied from 0.54±0.04 in Coastal to 0.63±0.03 in Barind sheep population. Genetic distance between Jamuna river basin and Barind was lowest (0.01) and between Garole and Costal was highest (0.17). Garoleand Chotonagpuri sheep has higher genetic distance from other three sheep populations. Phylogenetic dendogram showed that sheep of Jamuna river basin and barind were belonged to same genetic group. Whereas, coastal, garole and Nagpur sheeps were shown higher genetic distances from Jamuna river basin and coastal sheep. Considering findings of this study it may be concluded that the Barind and Jamuna river basin sheep belongs to a similar genetic group while, Garole and Coastal sheep are belonging to two distinct genetic groups. Bang. J. Anim. Sci. 2019. 48 (1): 17-22